ANALYSIS OF VOLTAGE CHANGES IN LOCAL LOW-VOLTAGE GRIDS WITH CONNECTED PHOTOELECTRIC PLANTS AND ASSESSMENT OF THE POSSIBILITY OF FORECASTING THESE CHANGES - Бацала, Ярослав; Федорів, Михайло; Живчин, Петро (SWorldJournal, 2024)
The article proposes to use models for forecasting the output power and productivity of a photovoltaic plant to analyze their impact on the change in voltage in the network. When modeling the operation of the power system with photovoltaic plants, it is